Hard Choices: How Does Injustice Affect the Ethics of Medical Aid in Dying? - Kious, Brent M. (Cambridge quarterly of healthcare ethics, 2024)
Critics of medical aid in dying (MAID) often argue that it is impermissible because background social conditions are insufficiently good for some persons who would utilize it. I provide a critical evaluation of this view. I suggest that receiving MAID is a sort of "hard choice," in that death is prima facie bad for the individual and only promotes that person’s interests in special circumstances. Those raising this objection to MAID are, I argue, concerned primarily about the effects of injustice on hard choices. I show, however, that MAID and other hard choices are not always invalidated by injustice and that what matters is whether the injustice can be remediated given certain constraints. Injustice invalidates a hard choice when it can, reasonably, be remedied in a way that makes a person’s life go better. I consider the implications of this view for law and policy regarding MAID.